Pneumatoceles and pneumothoraces complicating staphylococcal pneumonia: treatment by synchronous independent lung ventilation. Issue 5 (May 1993) - Lohse, A W; Klein, O; Hermann, E; Löhr, H; Kreitner, K F; Steppling, H; Meyer zum Büschenfelde, K H; Staritz, M
Abstract : A 54 year old man with a staphylococcal sepsis developed staphylococcal pneumonia complicated by multiple pneumatoceles and bilateral tension pneumothoraces caused by bronchopleural fistulae. Excessive enlargement of the right sided pneumatoceles and a tension pneumothorax not improved by drainage led to mediastinal shift and compression of the right lung. Reversal of the mediastinal shift and closure of the bronchopleural fistulae was achieved by assisted independent lung ventilation.